Instructor Authoring Tool for Creating E-Learning Content Using Learning Objects - Khairul Adilah, Ahmad (2005)
This thesis illustrates the conception of creating e-learning content. It is based on a research study with the aim to create a framework that can assist instructors to create e-learning content. This research presents the wage and approaches of XML and LCMS Component Technologies in the creation of IAT functional model and the development of IAT. XML can simplify the courseware authoring and structuring process. As a neutral meta-language, it can also separate course contents from course presentation. However, LCMS Component technology is a multi-user environment where instructors can create, store, reuse, manage, and deliver digital learning content from a central object repository. The use of XML and LCMS Component Technologies help a lot in adding the features of easy-to-use, easy-to-maintain, and flexibility to assist instructor to create e-learning content using IAT. This research employs courseware development research method, which aims to create IAT functional model and also develop IAT prototype system in order to help instructor create e-learning content. IAT allows instructors with non-programming skills to create e-learning content easily by using a template to customize their own course content.